Benefits and Challenges of Peer and Self-Assessment in Indonesian Vocational EFL Speaking Classrooms: Teachers’ Perspectives - Firman Ariyadi; Widyastuti Widyastuti; Slamet Setiawan (AL-ISHLAH: Jurnal Pendidikan, 2026)
Peer and self-assessment have been widely promoted as alternative assessment approaches that foster learner engagement and autonomy in English as a Foreign Language (EFL) classrooms. However, limited research has explored vocational EFL teachers’ perspectives on the implementation of these assessment practices in speaking classrooms, particularly in the Indonesian vocational education context. This qualitative case study investigated the perceptions of two English teachers at a vocational high school in Sidoarjo, Indonesia. Data were collected through semi-structured interviews, classroom observations, and document analysis of speaking assessment rubrics. The data were analyzed using thematic analysis to identify recurring patterns related to the benefits and challenges of peer and self-assessment. The findings revealed that teachers perceived peer assessment as promoting student engagement, collaborative learning, and awareness of speaking performance through observation and feedback. Self-assessment encouraged learner reflection, responsibility, and awareness of individual strengths and weaknesses. However, teachers also identified several challenges, including friendship bias and limited objectivity in peer assessment, as well as inaccurate self-evaluation resulting from insufficient assessment literacy and difficulties interpreting assessment criteria. The study suggests that the effectiveness of peer and self-assessment in vocational EFL speaking classrooms depends on structured implementation supported by clear assessment rubrics, explicit training in assessment practices, and continuous teacher guidance. These findings contribute to the growing literature on alternative assessment by providing context-specific insights into vocational EFL teachers’ perspectives and offer practical implications for designing more reliable and learner-centered speaking assessment practices.